Lasers : Generation of parabolic laser pulses in short fibre amplifiers. (21st October 2019) - Shchukarev, I A; Korobko, D A; Salganskii, M Yu; Zolotovskii, I O
Abstract: The laser pulse evolution in a normal-dispersion fibre amplifier is studied. The cases of ideal spectrum-homogeneous and transform-limited amplification are considered. It is shown that the envelope transformation of the input pulse to a parabolic form is possible not only for spectrally-flat amplification, but also for transform-limited one. In the latter case, an important parameter is the optimal amplifier length. The results demonstrate that, in the case of a sufficiently wide amplification spectrum, it is always possible to find the optimal amplifier length, after passing through which the output pulse envelope is close to a parabola.